Alternate partial root-zone irrigation combined with nitrogen fertilizer: An adaptive surge root irrigation and nitrogen strategy to improve apple yield, water-nitrogen use efficiency and fruit quality - Kun Hao; Wei Zhang; Shijiang Zhu; Youliang Peng; Yun Zhong; Feilong Jie; Lihua Liu; Yalin Gao; Lin Zhou; Chuang Liu; Fangyuan Shen (Agricultural Water Management)
A reasonable combination of water and nitrogen application under appropriate and use of water-saving irrigation techniques is essential for improving the apple quality and yield in the mountainous areas of the Loess Plateau. This study, which was conducted from 2019 to 2020, utilized seven-year-old Hanfu apples as experimental material. Its focus was on three factors: irrigation method, irrigation level, and nitrogen application level. An L9(34) orthogonal design comprised of nine treatments was employed. The three irrigation methods were unilateral fixed surge root irrigation (U), alternating surge root irrigation (A), and bilateral fixed surge root irrigation (B). The irrigation levels were 85 %–100 % θf (I1), 70 %–85 % θf (I2), and 55 %–70 % θf (I3). The nitrogen application levels were 600 kg N ha−1 (N1), 400 kg N ha−1 (N2), and 200 kg N ha−1 (N3). In the study, soil water and nitrogen distribution, yield, fruit quality, water and nitrogen utilization efficiency, physiological and reproductive indicators and economic benefit of apples under various surge root irrigation treatments were analyzed, and their responses to water and nitrogen management were explored. Principal component was used to assess assessed apple quality and the game theory-based combinatorial weighting method (TOPSIS) was used to provide comprehensive evaluation of apple yield, quality, and water-nitrogen utilization efficiency. The results showed apple yield, quality, water and nitrogen utilization efficiency, chlorophyll content, fresh treetop growth, and photosynthesis all to be significantly affected by irrigation methods, irrigation levels, and nitrogen application rates. High water and fertilizer conditions led to the highest chlorophyll content, fresh treetop growth rate, net photosynthesis rate, transpiration rate, and leaf instantaneous water use efficiency. Alternate irrigation was found to even perform well in moderate water and nitrogen conditions and it enhanced water and nitrogen use efficiency quite significantly. The respective chlorophyll a and b contents in the T1 treatment (UI1N1) were 35.15 % and 38.02 % higher than those in the T3 treatment (UI3N3), and both photosynthesis and transpiration rates exhibited significant increases. The Mantel test showed there to be a significant correlation between apple yield, various quality indicators, net photosynthesis rate, and transpiration rate (P < 0.05). The highest yield, overall quality, comprehensive evaluation, index net return and rate of return was produced by treatment T4 (AI1N2), while IWUE, WUE, and NPFP peaked in treatments T6 (AI3N1) and T5 (AI2N3). Range analysis showed that treatment AI2N1 to have the highest yield and comprehensive evaluation index, while treatment AI2N2 showed no significant difference in comparison to AI2N1. In addition, treatment AI2N2 exhibited the best overall quality, with WUE peaking in treatment AI2N1 and NPFP peaking in treatment AI2N3. Therefore, in terms of improving quality, increasing yield, rate of return and enhancing water and nitrogen use efficiency, the water-nitrogen regulation model for apples in the mountainous areas of the Loess Plateau under surge root irrigation that is most optimal is a combination of alternate irrigation and moderate water-nitrogen application (AI2N2 treatment). These findings provide a theoretical basis for further scientific research on subsurface root irrigation technology and water-nitrogen management in the cultivation of apples on the Loess Plateau.